Hypertensive patients show higher heart rate response during incremental exercise and elevated arterial age estimation than normotensive adult peers: VASCU-HEALTH PROJECT - Alvarez, Cristian; Campos-Jara, Christian; Ciolac, Emmanuel Gomes [UNESP]; Guimaraes, Guilherme Vega; Andrade-Mayorga, Omar; Cano-Montoya, Johnattan; Andrade, David C.; Delgado-Floody, Pedro; Alonso-Martinez, Alicia; Izquierdo, Mikel; Cigarroa, Igor (Federacion Espanola Asoc Docentes Educacion Fisica-feadef, 2023)
There is limited information regarding heart rate (HR) response from predictive formulae and actual exercise tests between arterial hypertension (HTN) and normotensive adults, as well as about vascular similarities or differences between samples of different blood pressure control. This study aimed 1) to describe and compare the HR during exercise between HTN and normotensive adults and 2) to describe the endothelial function and related vascular parameters in both groups. A descriptive clinical study was conducted with 64 adults (men and women) who were divided into three groups: arterial hypertension (HTN n=26), elevated blood pressure (Ele n=16), or normotensive control (CG n=22). The participants underwent an incremental cycling exercise test of 5 stages, where HR (primary outcome) was measured, and secondary vascular outcomes (percentile classification of the pulse wave velocity (%ILEPWVba), maximum carotid intima-media thickness (cIMTmax), and arterial age among others were measured. In stage 2 of the test (50100 watts), the HTN group showed significantly higher HR vs. CG (+14 beats/min; p<0.05) and vs. Ele group (+15 beats/ min; p<0.05), and in stage 5 (125-250 watts), HTN group showed higher HR vs. CG (+22 beats/min; p<0.05). HTN group showed a higher arterial stiffness by %ILEPWVba classification and arterial age estimation than the CG group. In conclusion, HTN patients reported a higher HR response only in two out of five (monitored) stages of the Astrand cycling exercise test than normotensive peers. Moreover, all groups showed a higher HRpredicted than real HRpeak obtained from the exercise test. These results are displayed with more altered vascular parameters in the HTN group.
Keywords: Arterial hypertension; Endothelial dysfunction; Overweight; Obesity; Vasculature